2019
DOI: 10.1088/1742-6596/1424/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

MOOC for Training: How Far It Benefits Employees?

Abstract: As the term 4th Industrial Revolution emerges globally, various industries are moving rapidly towards it. Malaysia, one of the developing countries, is also embracing the 4th Industrial Revolution. However, with the rapid development of industries to catch up to the ever-expanding world, the English proficiency of non-native speakers is worrying, especially in the working field. Certain industries provide training for their employees to improve their English for Occupational Purposes (EOP), but traditional tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Secondly, lack in skills related to lifelong learning (Anthonysamy, 2020;Sidhu et al, 2016;Williams, 2021). The same issues were also reported from the industrial side whereby students were reported lacking in the Lifelong Learning skills (Ghani & Mara, 2018;Rafiq et al, 2019;Wong et al, 2020). The importance of lifelong learning in education has been mentioned in several policies in Malaysia including the Blueprint on Enculturation of Lifelong Learning for Malaysia 2011-2020 (Ministry of Higher Education Malaysia, 2011), Malaysia Education Blueprint 2015-2025 (Higher Education) (Ministry of Higher Education Malaysia, 2015) and the government has allocated quite a budget to support this lifelong learning in education system.…”
Section: Introductionmentioning
confidence: 54%
“…Secondly, lack in skills related to lifelong learning (Anthonysamy, 2020;Sidhu et al, 2016;Williams, 2021). The same issues were also reported from the industrial side whereby students were reported lacking in the Lifelong Learning skills (Ghani & Mara, 2018;Rafiq et al, 2019;Wong et al, 2020). The importance of lifelong learning in education has been mentioned in several policies in Malaysia including the Blueprint on Enculturation of Lifelong Learning for Malaysia 2011-2020 (Ministry of Higher Education Malaysia, 2011), Malaysia Education Blueprint 2015-2025 (Higher Education) (Ministry of Higher Education Malaysia, 2015) and the government has allocated quite a budget to support this lifelong learning in education system.…”
Section: Introductionmentioning
confidence: 54%
“…Researchers pay attention to such advantages of MOOC as their mass character, lifelong education [23], their being fully or partially free of charge, a possibility to get access to educational material a lot of times, a free schedule for taking online courses [13], internationalization of education [24], independence from social status, a possibility to get a certificate [10], etc. MOOC is a means of branding for higher educational institutions [25], organizations and institutions of various levels whose employees participate in the development of online courses [26].…”
Section: Learning Programming With Online Coursesmentioning
confidence: 99%
“…Studying the issue of workplace training, particularly learning English for Occupational Purposes in MOOCs, K. Rafiq et al [29] give the following benefits of MOOCs both for employers and employees:…”
Section: Challenges Of Moocs For Teaching and Learning Foreign Languagesmentioning
confidence: 99%